1985
DOI: 10.21273/jashs.110.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 on Total Phenolics, Phenylalanine Ammonia Lyase, and Polyphenol Oxidase in Lettuce Tissue

Abstract: An atmosphere of air + 15% CO2 caused CO2 injury in lettuce (Lactuca sativa L.) in about 10 days at 0°C. However, subsequent removal of CO2 was necessary for the brown stain symptoms to develop. Under CO2 treatment, phenylalanine ammonia lyase (PAL) was induced and its activity correlated well with the development of the injury. Nevertheless, PAL activity did not seem responsible for the differences in susceptibility to CO2 injury among the 3 lettuce cultivars included in this study. Prevention of the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 14 publications
1
10
1
1
Order By: Relevance
“…The reason for the later decrease in PAL activity is unclear. Similar results were observed by Hyodo et al (1978) and by Siriphanich and Kader (1985a) when lettuce tissue was kept at higher temperatures during exposure to inducing atmospheres; the authors suggested that this might be a result of the development of a PAL-inactivating system such as the one proposed by Zucker (1968).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The reason for the later decrease in PAL activity is unclear. Similar results were observed by Hyodo et al (1978) and by Siriphanich and Kader (1985a) when lettuce tissue was kept at higher temperatures during exposure to inducing atmospheres; the authors suggested that this might be a result of the development of a PAL-inactivating system such as the one proposed by Zucker (1968).…”
Section: Discussionsupporting
confidence: 73%
“…Wrapper leaves were discarded and the next eight to 12 uninjured leaves were used. Previous studies have shown that basal midrib tissue was most sensitive to C 0 2 (Siriphanich and Kader, 1985a). Therefore, midrib segments * 2 cm wide and extending 4 cm up the leaf were excised starting 1 cm from the base of each leaf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf disks of about 27 mm in diameter were taken from the midrib area of leaves located one-third to two-thirds the distance from the cap leaf to the core. Tissue from this area is the most sensitive to C 0 2 injury (3,24). Green leaf disks were taken from wrapper leaves.…”
Section: Methodsmentioning
confidence: 99%
“…C 0 2 is known to inhibit browning of physically-damaged plant tissues by inhibiting the activity of polyphenol oxidase (PPO) and lowering the level of phenolic compounds (4,12). However, the mechanism by which C 0 2 reduces phenolic content is not fully understood; it may or may not be related to the browning process.…”
mentioning
confidence: 99%